Pengaruh Kualitas Pelayanan Dan Keluhan Terhadap Kepuasan Pelanggan Air Minum Bersih PDAM (BUMDes) Di Desa Tanarawa Kecamatan Waiblama Kabupaten Sikka - Marianus Oswaldus; Antonius Phillipus K.Gheta; Dimas Realino (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
Water is a basic, irreplaceable human need, so its management must be effective, efficient, and sustainable. The Tanarawa Village Government, through the Village-Owned Enterprise (BUMDes), manages the Regional Drinking Water Company (PDAM) to meet the community's clean water needs. However, various obstacles remain, ranging from suboptimal water quality, uneven distribution, and customer complaints. This situation raises questions about the extent to which service quality and complaints influence customer satisfaction at the Tanarawa Village PDAM, Waiblama District, Sikka Regency. This study aims to: (1) describe the service quality of the Tanarawa Village PDAM, (2) identify the types of complaints submitted by customers, and (3) analyze the influence of service quality and complaints on customer satisfaction. The research method used was a descriptive quantitative approach using a survey technique. Data were collected through questionnaires from 30 respondents who were customers of the Tanarawa Village PDAM. Data analysis included validity and reliability tests, multiple linear regression analysis, hypothesis testing, and coefficient of determination. The results of the study, based on descriptive analysis, indicate that service quality, complaints, and satisfaction are categorized as "Good," although there are still shortcomings in response speed, consistency of water distribution, and staff reliability. Customer complaints predominantly concern frequent interruptions in water flow, poor water quality, and slow response times, requiring improvement to Very Good. Statistical analysis of the effect of service quality on customer satisfaction shows a t_(count) > t_table = 3.325 > 1.99, concluding that service quality significantly influences customer satisfaction. Furthermore, statistical analysis of the effect of complaints on customer satisfaction also yielded a t_(count) > t_table = 3.917 > 1.99, concluding that customer complaints have a significant impact on satisfaction levels. Thus, this study confirms that consistent improvements in service quality and prompt and resolute complaint handling are important factors in increasing customer satisfaction. The results are expected to provide strategic input for the Tanarawa Village Water Company (PDAM) in improving its service system and strengthening relationships with the community.